(untitled) (Dhaka University Journal of Science, 2022)
Simulation of Super Cyclonic Storm (SuCS) Amphan (2020) has been carried out as a case study to analyze the sensitivity of Initial Condition (IC) and Horizontal Resolution (HR) on the intensity, track, and landfall predictions of the Tropical Cyclones (TCs). The results suggest that the IC and HR have a significant impact on TC simulations. Diminishing the HR in simulation results in a comparatively higher severity of the system. The simulation with a reduced lead time and a comparatively smaller HR has forecasted the Minimum Central Pressure (MCP) distribution reasonably well. In comparison to the observations, the reduced lead time model run with higher resolution has forecasted the Maximum Sustained Wind Speed (MSWS) distribution precisely. According to the statistical analysis, the continual reduction of lead time in simulation with the HR of 27 km has simulated better track and landfall positions than other resolutions. Thus, the combination of reduced lead time and higher resolution in simulation may be considered for the proper track and landfall forecasting. Dhaka Univ. J. Sci. 69(3): 202-211, 2022 (June)